In Bergomi [Stochastic Vol Modelling] (Sec. 2.5.2), in the section on surface dynamics, the following definition of the "Skew Stickiness Ratio" (SSR) is made:

$$ SSR = \dfrac{1}{\mathcal{S}_T}\frac{d\hat{\sigma}_{F_TT}}{d\log(S_0)}$$

where $\mathcal{S}_T=\frac{d\hat{\sigma}_{KT}}{d\log{K}}\Bigr\rvert_{K=F_T}$.

Combining these equations we get,

$$ SSR = \dfrac{1}{\frac{d\hat{\sigma}_{KT}}{d\log{K}}\Bigr\rvert_{K=F_T}}\frac{d\hat{\sigma}_{F_TT}}{d\log(S_0)}$$

Then Bergomi says that $SSR=1 =>$ Sticky Strike and $SSR=0 =>$ Sticky Delta.

I would like to prove these statements mathematically, but I am having trouble.

If $SSR=1$, then we have that: $$ \frac{d\hat{\sigma}_{KT}}{d\log{K}}\Bigr\rvert_{K=F_T}= \frac{d\hat{\sigma}_{F_TT}}{d\log(S_0)}$$

then how is this statement equivalent to sticky strike? In other words, how is this statement equivalent to $\hat{\sigma}_{KT}(t,S_t)=\hat{\sigma}_{KT}(t+\epsilon, S_{t+\epsilon})$?

If $SSR=0$, then we have that: $$ \frac{d\hat{\sigma}_{F_TT}}{d\log(S_0)}=0$$

then how is this statement equivalent to sticky delta? In other words, how is this statement equivalent to $\hat{\sigma}_{xT}(t,S_t)=\hat{\sigma}_{xT}(t+\epsilon, S_{t+\epsilon})$, where $x=\log{\dfrac{S}{F_T}}$?

Bergomi gives intuitive explanations for these statements which don't make much sense to me. I suppose I am looking for a formal proof to ease my mind.


1 Answer 1


Some Notations

It's easy to get lost so let's introduce some notations and let $$ \sigma : (t, S, K, \tau) \to \sigma(K,\tau; S, t) $$ denote the implied volatility smile prevailing at time $t$ when the spot price is $S_t=S$ for an option with strike level $K$ and time to expiry $\tau=T-t$. From here onward, we drop the $t$ argument to keep notations uncluttered (everything happens at fixed $t$).

Back to the notations used in the book, the ATMF vol for the current ($t=0$) spot value of $S_0$ can then be rewritten as $$ \hat{\sigma}_{F_T T}(S_0) := \sigma(f(S_0),T; S_0) $$ where the forward price verifies $$F_T := f(S_0) = S_0 \exp((r-q-u)T)$$

Using these notations, the second term involved in the definition of the SSR can be readily evaluated as $$ \frac{ d \hat{\sigma}_{F_T T}(S_0) }{d S_0} = \lim_{\epsilon \to 0} \frac{\color{blue}{\sigma(f(S_0+\epsilon),T; S_0+\epsilon)}- \color{green}{\sigma(f(S_0),T ; S_0)} }{ \epsilon } $$

The stickiness assumptions allow us to relate the smile after a spot move $\color{blue}{\sigma(\cdot,T;S_0+\epsilon)}$ to the original smile $\color{green}{\sigma(\cdot,T;S_0)}$. In particular

Sticky strike rule

For all $K>0$ we by definition need to have $$\color{blue}{\sigma(K,T;S_0+\epsilon)} = \color{green}{\sigma(K,T;S_0)}$$ such that we can successively write \begin{align} \frac{ d \hat{\sigma}_{F_T T}(S_0) }{d S_0} &= \lim_{\epsilon \to 0} \frac{\color{blue}{\sigma(f(S_0+\epsilon),T; S_0+\epsilon)} - \color{green}{\sigma(f(S_0),T ; S_0)} }{ \epsilon } \\ &= \lim_{\epsilon \to 0} \frac{\color{green}{\sigma(f(S_0+\epsilon),T; S_0)} - \color{green}{\sigma(f(S_0),T ; S_0)} }{ \epsilon } \\ &= \frac{\partial \sigma(K,T;S_0)}{\partial K}(f(S_0)) f'(S_0) \end{align} Since from the definition of $f(.)$ we have $$ f'(S_0) = f(S_0)/S_0 $$ then indeed $$ \frac{ d \hat{\sigma}_{F_T T}(S_0) }{d \ln(S_0)} = \frac{\partial \sigma(K,T;S_0)}{\partial \ln(K) }(f(S_0)) = \mathcal{S}_T $$

Sticky moneyness rule

By definition $$ \sigma(K^*,T;S_0+\epsilon) = \sigma(K,T;S_0) $$ if and only if $K^*/(S_0+\epsilon) = K/S_0$.

Hence the equivalent formulation of the rule, for all $K > 0$ $$ \color{blue}{\sigma(K,T,S_0+\epsilon)} = \color{green}{\sigma(K S_0/(S_0+\epsilon), T; S_0)} $$

Applying this now leads to \begin{align} \frac{ d \hat{\sigma}_{F_T T}(S_0) }{d S_0} &= \lim_{\epsilon \to 0} \frac{\color{blue}{\sigma(f(S_0+\epsilon),T; S_0+\epsilon)} - \color{green}{\sigma(f(S_0),T ; S_0)}}{ \epsilon } \\ &= \lim_{\epsilon \to 0} \frac{\color{green}{\sigma(f(S_0+\epsilon) S_0/(S_0+\epsilon),T; S_0)} - \color{green}{\sigma(f(S_0),T ; S_0)} }{ \epsilon } \\ &= \lim_{\epsilon \to 0} \frac{\color{green}{\sigma(f(S_0),T; S_0)} - \color{green}{\sigma(f(S_0),T ; S_0)} }{ \epsilon } = 0 \end{align}

  • $\begingroup$ Very clear and rigorous $\endgroup$
    – John Doe
    Commented Apr 11, 2018 at 17:33
  • 1
    $\begingroup$ Glad I could help $\endgroup$
    – Quantuple
    Commented Apr 11, 2018 at 17:37
  • $\begingroup$ @Quantuple: Nice answer +1. Would you care to take a look at this question quant.stackexchange.com/q/39202/6686 ? Thanks. $\endgroup$
    – Hans
    Commented Apr 12, 2018 at 20:50
  • $\begingroup$ in the sticky strike derivation, I think the equation in the third line should be ∂σ(K,T;S0)/∂K * (∂K/∂S0), where ∂K/∂S0 = K/S0 $\endgroup$
    – Yanyi Yuan
    Commented Mar 28 at 14:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.